New developments in immunotherapy for SCLC - Zhonglin Hao; Tsering Dolkar; Christopher Gates; Reinhold Munker (Journal for ImmunoTherapy of Cancer)
Small cell lung cancer (SCLC) is an aggressive form of neuroendocrine neoplasm known for its striking initial response to treatment, followed by fast relapse and refractoriness in response to additional lines of therapy. New advances in immunotherapy are paving the way for more effective treatment strategies and have promising results with early clinical trial data. While SCLC rarely harbors actionable mutations, the receptor DLL3 is extensively present in SCLC, making it a potential target for immunotherapy. Three emerging therapeutic options include bispecific T cell engagers targeting DLL3, chimeric antigen receptor T cells (CAR-T cells), and antibody–drug conjugates. Several phase II and phase III clinical trials for bispecific T cell engagers show promise. Additionally, the first CAR-T cell trials in humans for SCLC are currently underway.